Development and validation of an ionic chromatography method for nitrite determination in processed foods and estimation of daily nitrite intake in Korea. (15th July 2022) - Lim, Ho Soo; Lee, Sang Jin; Choi, Euna; Lee, Soo Bin; Nam, Hye Seon; Lee, Jong Kwon
Highlights: A simple ionic chromatography method for nitrite analysis was developed and validated. Nitrite contents in 60 processed food products were analyzed by applying the method. The estimated daily intake of nitrite for general population in Korea was at a safe level. The proposed method was suitable for nitrite analysis and exposure assessment in foods. Abstract: A simple ionic chromatography method for nitrite analysis in processed food products was developed and validated. Nitrite in the sample was extracted using 80 °C distilled deionized water and centrifuged. Purification of nitrite from sample solution was performed using OnGuard II Ag, OnGuard II RP and OnGuard II Na cartridge connected in order. Determination of nitrite was carried out using IonPac AG9-HC (4 × 50 mm) and IonPac AS9-HC (4 × 250 mm) columns and a 9 mM sodium carbonate mobile phase. The validated results showed good linearity ( r 2  > 0.999), recoveries (83.7–107.6%) and precision (1.3–5.1%). The levels of nitrite in processed food products were between n.d. to 33.5 mg/kg, and nitrite was detected in ham, sausage and bacon products. The mean nitrite intake was 2.7% of the Acceptable Daily Intake (ADI, 0.07 mg/kg bw/day) for the Korean population. The method was suitable for the analysis of nitrite in processed foods.